2002
DOI: 10.1063/1.1503852
|View full text |Cite
|
Sign up to set email alerts
|

Lateral-cavity spectral hole burning in quantum-dot lasers

Abstract: Spectral hole burning effects are observed as strong spectral intensity modulations in the emission spectra of broad and narrow stripe quantum-dot lasers with ridge waveguide. The modulation is attributed to lateral-cavity resonances burning holes in the inhomogeneously broadened spectral gain profile of the quantum dots. Lateral cavity engineering is expected to be crucial for optimizing quantum-dot laser performance and for potential realizing of wavelength-stabilized devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…The presence of an additional resonance constraint that imposes this broader spectral selectivity is more likely. Similar spectral observations have been reported for lasers based on a dye solution in a cuvette and a quantum-dot waveguide, and in both cases the lateral dimensions of the waveguide were considered responsible for this wavelength selectivity [16,17]. In other work, longitudinal mode grouping has been attributed to interference effects with substrate modes leading to a wavelength dependent depletion of the net-gain, but also linked to the linewidth of the homogenously broadened laser transition [18,19].…”
Section: Spectral Selectivitysupporting
confidence: 73%
“…The presence of an additional resonance constraint that imposes this broader spectral selectivity is more likely. Similar spectral observations have been reported for lasers based on a dye solution in a cuvette and a quantum-dot waveguide, and in both cases the lateral dimensions of the waveguide were considered responsible for this wavelength selectivity [16,17]. In other work, longitudinal mode grouping has been attributed to interference effects with substrate modes leading to a wavelength dependent depletion of the net-gain, but also linked to the linewidth of the homogenously broadened laser transition [18,19].…”
Section: Spectral Selectivitysupporting
confidence: 73%
“…This is possible in a carrier deficient system (i.e., the QCW mode) where the possibility of thermal carrier spillover is high leading to non-uniform thermal re-distribution of carriers among Qdash stacks that would affect the active region gain, and hence the lasing spectra. Note that the spectral position of the low intensity gap depends on the drive current and therefore we rule out the possibility of any lateral cavity resonances [17] or leaky substrate modes [18] in our device that might cause such anomalous observation. However, we cannot exclude the possibility of different non-linear phenomena occurring in the active region that affects the lasing spectra, particularly, the spectral and spatial hole burning effects which intensifies with continuous surge of carriers and/or temperature rise.…”
Section: Device Characterizationmentioning
confidence: 95%
“…Detailed studies of the dependence of the characteristic separation between the valleys in the lasing spectrum on the ridge stripe width of QD lasers was done in [ 39 ]. It was clearly shown that the mode group spacing strongly increases with decrease in the ridge stripe width, evidencing the impact of the transverse cavity effect.…”
Section: Longitudinal Mode Grouping In Qd Lasersmentioning
confidence: 98%